2007
DOI: 10.1021/jm0708533
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluorinated Derivatives of the Broad-Spectrum MMP Inhibitors N-Hydroxy-2(R)-[[(4-methoxyphenyl)sulfonyl](benzyl)- and (3-picolyl)-amino]-3-methyl-butanamide as Potential Tools for the Molecular Imaging of Activated MMPs with PET

Abstract: An approach to the in vivo imaging of locally upregulated and activated matrix metalloproteinases (MMPs) found in many pathological processes is offered by positron emission tomography (PET). Hence, appropriate PET radioligands for MMP imaging are required. Here, we describe the syntheses of novel fluorinated MMP inhibitors (MMPIs) based on lead structures of the broad-spectrum inhibitors N-hydroxy-2(R)-[[(4-methoxyphenyl)sulfonyl](benzyl)-amino]-3-methyl-butanamide (CGS 25966) and N-hydroxy-2(R)-[[(4-methoxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 31 publications
0
68
0
Order By: Relevance
“…The study of this model showed that clinically relevant imaging parameters may miss diffusely infiltrative glioblastoma in the absence of vascular remodeling, thus necessitating the development of improved imaging protocols for diffusely infiltrating tumor cells (e.g., the use of markers for activated matrix metalloproteinases (40), the use of 18 F-3,4-dihydroxyphenylalanine (38,39), or the use of higher dose of 18 F-FLT (30)). As has been detailed by Dhermain et al (9), MRI is the imaging method of choice for patients with gliomas, for whom additional PET (in conjunction with MRI) may reveal important complementary information with regard to detection of hot spots in low-grade lesions; planning of biopsy, surgery, and radiation; and detection of recurrent tumors (9).…”
Section: Discussionmentioning
confidence: 99%
“…The study of this model showed that clinically relevant imaging parameters may miss diffusely infiltrative glioblastoma in the absence of vascular remodeling, thus necessitating the development of improved imaging protocols for diffusely infiltrating tumor cells (e.g., the use of markers for activated matrix metalloproteinases (40), the use of 18 F-3,4-dihydroxyphenylalanine (38,39), or the use of higher dose of 18 F-FLT (30)). As has been detailed by Dhermain et al (9), MRI is the imaging method of choice for patients with gliomas, for whom additional PET (in conjunction with MRI) may reveal important complementary information with regard to detection of hot spots in low-grade lesions; planning of biopsy, surgery, and radiation; and detection of recurrent tumors (9).…”
Section: Discussionmentioning
confidence: 99%
“…25 Analog to compound 2a and 2b the second aromatic ring of compound 3 was The benzylamines used for the synthesis of the MMP-13 inhibitors are represented in Scheme 1. Starting from commercially available 4-hydroxybenzylamine different psubstituted benzylamines were prepared by protection of the amine, substitution reaction with 2-fluoroethyl 4-methylbenzenesulfonate, 26 ethane-1,2-diyl bis(4-methylbenzenesulfonate), 2-7 azidoethyl 4-methylbenzenesulfonate 27 or 3-bromoprop-1-yne and deprotection of the amine with 4 HCl in dioxane. The alkyne substituted BOC-protected amide 6e was subjected to a copper(I) catalyzed click reaction with 1-azido-2-fluoroethane.…”
Section: Resultsmentioning
confidence: 99%
“…1-azido-2-fluoroethane, 32 and 2-fluoroethyl 4-methylbenzenesulfonate 33 were synthesized following literature procedures. All animal experiments were approved by the North RhineWestphalia Agency for Nature, Environment, and Consumer Protection (Landesamt für Natur, Umwelt und Verbraucherschutz Nordrhein-Westfalen-LANUV).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with substrates, inhibitors interact with MMPs in a 1:1 manner and have no signal magnification. Research groups established two nonpeptidic MMP inhibitor-based probes (hydroxamates and barbiturates) to evaluate MMP activity and obtain an ideal outcome (90)(91)(92). By using this approach, MMP inhibitors can be used for imaging targets.…”
Section: Mmpmentioning
confidence: 99%